Ozeki's A Tale for the Time Being: The Value of Heritage Through Private Writings - Cisneros, Pamela (Université d'Ottawa | University of Ottawa, 2022)
This article considers the representation of kikokushijo, or Japanese returnees, in Ruth Ozeki's A Tale for the Time Being through the eyes of her protagonist, Nao Yasutani. In the months prior to the 2011 Tōhoku earthquake and tsunami, the novel considers Nao's struggles to belong as a young woman who returns to her homeland as a Japanese national from abroad along with her resistance to view her heritage language - Japanese - in a favorable light. Her reflections lead to a personal exploration of Japan's reception of citizens from abroad and her own family history. These factors spark an interest in keeping a diary, one that becomes the catalyst for Nao to appreciate her individuality.
Keywords: kikokushijo; Ruth Ozeki; family; heritage language; discrimination; Zen Buddhism